Da'wa, Keris, and Community Elites in Java - Ismail, Muchammad; Mu'adi, Sholih (Proceedings of International Conference on Da'wa and Communication, 2021)
The keris is recognized as an heirloom by the people of the archipelago until now it is still interesting to study. Why is that. It is undeniable that many people are pro and contra of the keris cultural heritage. This study is to see people’s view on Keris. This study uses a qualitative approach with a phenomenological approach. One of the research methods used is participant observation The results of the data findings there are three discussions, among others; a) the history of the keris has existed since the Hindu-Buddhist era in Java. Keris comes from the Keker language and Aris Kekeran means fence (barrier, warning, control). Meanwhile, Aris means calm, steady, smooth. b) Keris in the Islamic perspective, Islam does not prohibit owning a keris because it is an asset of cultural capital in religion for preaching by the elite of society. c) the form of elite behavior in the possession of a keris there is a moderating attitude that the keris must be preserved to the community including the elite making it the object of the keris as a medium of da'wah d). keris as a moral and ethical symbol, during the movement of the Walisongo the keris was not just a noble iron aji, but in it contained the values ​​and philosophy of the meaning of exemplary life, the keris for its owner was the embodiment of prayer to God by the master to the owner of the keris.